2019
DOI: 10.1177/0040517519871943
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental study of the bursting performance of triaxial woven fabric and its reinforced rubber composites

Abstract: In this paper, the bursting performance of triaxial woven fabric and its reinforced rubber composites are studied by the finite element method and the experimental approach, and compared with plain woven fabric and its reinforced rubber composites. The bursting morphologies and load–displacement curves of the specimens during the bursting process are obtained. The results indicate that the rubber matrix has a protective and consolidation effect on the inner fabric, significantly improving the bursting strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The achievements along this thread include the solid-shell finite element proposed to solve such major issues as large free-hanging lengths, extensive folds and fabric-to-solid contact, 9 the mesoscale methodology for the drape of biaxial non-crimp fabric allowing individual tow and stitch deformations and their interaction, 10 the discrete Kirchhoff frame avoiding interpenetration between different parts of the virtual fabric, 11 the non-orthogonal constitutive code as well as the lay-up shell model, which is capable of describing the bending properties of fabric in various directions, 12 the fibrous quasi-inextensibility algorithm to efficiently calculate the transverse shear strain in textile composites 13 and the morphological approach to investigating the bursting process of triaxial woven fabric composites. 14 In a mass-spring system, however, the fabric is dispersed into a set of mass points that are connected to each other by assumed springs that manifest elasticity and damping. The forces inside the fabric are mainly determined by the elastic coefficients as well as the relative displacements within the group.…”
mentioning
confidence: 99%
“…The achievements along this thread include the solid-shell finite element proposed to solve such major issues as large free-hanging lengths, extensive folds and fabric-to-solid contact, 9 the mesoscale methodology for the drape of biaxial non-crimp fabric allowing individual tow and stitch deformations and their interaction, 10 the discrete Kirchhoff frame avoiding interpenetration between different parts of the virtual fabric, 11 the non-orthogonal constitutive code as well as the lay-up shell model, which is capable of describing the bending properties of fabric in various directions, 12 the fibrous quasi-inextensibility algorithm to efficiently calculate the transverse shear strain in textile composites 13 and the morphological approach to investigating the bursting process of triaxial woven fabric composites. 14 In a mass-spring system, however, the fabric is dispersed into a set of mass points that are connected to each other by assumed springs that manifest elasticity and damping. The forces inside the fabric are mainly determined by the elastic coefficients as well as the relative displacements within the group.…”
mentioning
confidence: 99%
“…The finite element models were developed by Solidworks ® 2015 5 based on the yarn cross-sectional shape and yarn trajectory in TWFR, as shown in Figure 5.…”
Section: Geometric Modelmentioning
confidence: 99%
“…The results showed that TWF and TWFR had more isotropic responses to both bursting and shear deformations compared with conventional woven fabric reinforced flexible composites. [5][6][7] Therefore, it is also necessary to study the anisotropic properties of TWFreinforced flexible composites.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al [ 15 ] used the finite element method to study the effects of yarn inclination, yarn friction, and tensile modulus on yarn properties. Zhou et al [ 16 ] used the finite element method to study the blasting performance of fabric-reinforced rubber composites and found that the rubber improved the breaking strength of the fabric. Sun et al [ 17 ] tested the puncture behavior of various structures using finite element analysis.…”
Section: Introductionmentioning
confidence: 99%